Assessment of clinical profile, antibiotic sensitivity and prescription pattern in blood culture positive enteric fever among pediatric and adult patients admitted in a tertiary care hospital: a prospective study - Gautam, Swapnil; Purushothaman, Suraj; Patel, Kinjal P.; Sankhe, Ajay P.; Mahadik, Madhuri R. (International Journal of Research in Medical Sciences, 2019)
Background: Asterion Introduction: Enteric fever is a major concern in developing country. It is predominantly caused by serovars typhi and paratyphi of Salmonella enterica. Recently, an upsurge in antimicrobial resistant strains has worsened the management of enteric fever. So, aim of present study is to evaluate the clinical profile, antibiotic sensitivity and prescription pattern in blood culture proven cases of enteric fever in pediatric and adult patients. Methods: Single centre, prospective study was conducted at a tertiary care hospital. Demographic and clinical details of blood culture proven enteric fever admitted in hospital were collected over the period from August 2016 to November 2018. Results: Total 58 blood cultures grew Salmonella spp. , amongst them 84.48 % had growth of Salmonella typhi. Blood culture was sent after a mean period of 9 days and 10 days of fever in pediatric and adult patients respectively. All isolates of S. paratyphi A were pansusceptible, whereas 36.73 % isolates of S. typhi were multidrug resistant and nalidixic acid resistant. 68.97% patients received antibiotics before admission. The difference between mean time to defervescence in patients who received ceftriaxone and those who received more than one antibiotic was not statistically significant. (P value 0.87) Conclusion: Blood cultures are the important diagnostic tool to identify multidrug resistant Salmonellae. Study showed that combination therapy was not statistically superior and awareness of local antimicrobial susceptibility pattern significantly helps for better management of the patients.